Whole-Genome Analysis of Three Yeast Strains Used for Production of Sherry-Like Wines Revealed Genetic Traits Specific to Flor Yeasts - Eldarov, Mikhail A.; Beletsky, Alexey V.; Tanashchuk, Tatiana N.; Kishkovskaya, Svetlana A.; Ravin, Nikolai V.; Mardanov, Andrey V. (Frontiers in Microbiology, 2018)
Flor yeast strains represent a specialized group of Saccharomyces cerevisiae yeasts used for biological wine ageing. We have sequenced the genomes of three flor strains originated from different geographic regions and used for production of sherry-like wines in Russia. According to the obtained phylogeny of 118 yeast strains, flor strains form very tight cluster adjacent to the main wine clade. SNP analysis versus available genomes of wine and flor strains revealed 2270 genetic variants in 1337 loci specific to flor strains. Gene ontology analysis in combination with gene content evaluation revealed a complex landscape of possibly adaptive genetic changes in flor yeast, related to genes associated with cell morphology, mitotic cell cycle, ion homeostasis, DNA repair, carbohydrate metabolism, lipid metabolism, and cell wall biogenesis. Pangenomic analysis discovered the presence of several well-known “non-reference” loci of potential industrial importance. Events of gene loss included deletions of asparaginase genes, maltose utilization locus, and FRE-FIT locus involved in iron transport. The latter in combination with a flor yeast-specific mutation in the Aft1 transcription factor gene is likely to be responsible for the discovered phenotype of increased iron sensitivity and improved iron uptake of analyzed strains. Expansion of the coding region of the FLO11 flocullin gene and alteration of the balance between members of the FLO gene family are likely to positively affect the well-known propensity of flor strains for velum formation. Our study provides new insights in the nature of genetic variation in flor yeast strains and demonstrates that different adaptive properties of flor yeast strains could have evolved through different mechanisms of genetic variation.